Surface integrity and fatigue properties of Ti–6Al–4V alloy under the ultrasonic surface rolling process excited strain rate effect - Zha, Xuming; Qin, Hao; Yuan, Zhi; Xi, Linqing; Chen, Xiao; Li, Yi; Jiang, Qingshan; Xu, Zhilong; Jiang, Feng (Journal of materials research and technology, 2025)
Ultrasonic surface rolling process is a novel surface enhancement technique that significantly influences the surface integrity and fatigue performance of titanium alloys. In this study, the ultrasonic impact strengthening mechanism was researched by single-point ultrasonic impact strengthening experiment and verified in ultrasonic surface rolling process under actual working conditions. The effects of different ultrasonic impact amplitudes on the deformation strain rate, surface morphology, microstructure, hardness field and residual compressive stress field of Ti–6Al–4V workpieces after USRP were investigated. In the process of single point ultrasonic impact, the impact kinetic energy applied to the workpiece surface is positively correlated with the ultrasonic amplitude, and this could lead to a high strain rate plastic deformation of the material surface. After USRP treatment, the hardness distribution of the workpiece in the depth direction shows a trend of first increasing and then decreasing until it reaches the hardness level of the substrate. Compared with the deeper layer deformed region, the number of low-angle grain boundaries (LAGB) was larger at the surface layer of workpiece, which indicates that the degree of grain refinement is significantly improved. The fatigue failure mechanisms and the characteristics of fatigue crack initiation and propagation were studied. Under the condition of ultrasonic amplitude of 4 μm, the fatigue life of Ti–6Al–4V workpiece after USRP could reach about 7,529,116 cycles. This study could provide effective guidance for the mechanisms of ultrasonic impact strengthening and the selection of appropriate ultrasonic impact parameters for titanium alloy workpiece.